Genetic Diversity of Some Sweet Cherry Cultivars Based on Molecular Markers - Ioana Virginia Berindean (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2016)
Sweet cherry (Prunus avium L.), originated around the Caspian and Black Sea, is an important fruit tree species of economic interest, and hence, breeding and conservation are requested (. Genetic analysis at the molecular level can be used effectively to study molecular polymorphism existing between intraspecific and interspecific tree species and phylogenetic relationships between them and their hybrids. The purpose of this study was to characterize and determine genetic relationships among the sweet cherry native genotypes belonging to Fruit Research & Development Station Bistrita, Romania, using RAPD markers. To eliminate the existence of possible synonyms from national romanian collection, we collect four Van cultivars, from four different national collection. For molecular analysis of the 16 varieties of sweet cherry were considered 13 RAPD primers selected from the literature. They were later used to determine the genetic variability at the molecular level using PAST program, and the dendrogram was generated based on Jaccard’s genetic distance. The dendrogram constructed by PAST software. The quantity and quality of the DNA obtained was suitable to achieve PCR amplification step. Only seven out of the 13 RAPD primers have generate polymorphic bands. The rest of seven were monomorphics. The most polymorphic primer was OPB10 which generated 11 bands from which 100% were polymorphic.Seven RAPD primers generated a high level of polymorphism which allowed to divide these cherry varieties into two groups according to their genetic geographical origin and the pedigree.